PENEGAKAN HUKUM TERHADAP WARGA NEGARA ASING YANG MELAKUKAN TINDAK PIDANA ASUSILA DI DESTINASI WISATA - Dewa Ayu Julia Anastasya; Ida Ayu Putu Widiati; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2024)
Immoral acts by foreigners in tourist destinations must receive sanctions based on regulations in the Criminal Code and sanctions based on customary law. The problem is, 1) what are the legal regulations for foreigners who commit immoral acts in tourist destinations? and 2) How the judge considered decision Number 66/Pid.B/2021/PN. Sgr about immoral crimes committed by foreigners in tourist destinations? This research describes the legal regulations and considerations of judges in deciding cases of acts of decency by foreign citizens in tourist destinations. This research uses deductive legal logic which is analyzed descriptively through a statute approach, conceptual approach and case approach. This research shows that the legal regulations for foreigners who carry out decency acts in tourist destinations are part of the regulations for decency acts in the Criminal Code and customary law. The judge's decision considerations are based on legal and non-legal factors. The relationship between the two lies in the application of criminal sanctions and the judge's consideration in making a decision.